The effect of some social media webs on the feeling of psychological safety on a Sample of Um Al-Qura University Students - Al-Sharif, Walaa Mansour Nasser (Journal of Educational and Psychological Sciences, 2022)
This research aimed at examine the effect of some social networks on the feeling of psychological security among a sample of Umm Al-Qura University students. The researcher used the social networking scale and the psychological security scale, applied randomly on a sample of (150) Umm Al-Qura University students, during the year 1443 AH. As a result, there were statistically significant differences between the mean scores of the sample members in the use of social networks according to the gender variable in favour of females, and there were differences in the mean scores of the sample members in the use of social networks according to the educational stage variable, which were in favour of those with a bachelor’s degree. There were also statistically significant differences between the mean scores of the sample members in psychological security according to the gender variable favouring females, as well as differences in the mean scores of the sample members in psychological security according to the study stage variable, in favour of postgraduate stage. There was also direct correlation proportionality between the questionnaire on the use of social networks and the psychological security questionnaire during the Corona pandemic. Accordingly the researcher recommended enhancing positive feelings among Umm Al-Qura University students and to benefit from psychological and social counselling centres in developing students and strengthening their skills to achieve psychological security during crises.